Effect of Different Soil Moisture Regime on the Yield and Yield Components of Onion (Bangladesh Journal of Scientific and Industrial Research, 2007)
No abstract available.Bangladesh J. Sci. Ind. Res. 41(1-2), 109-112, 2006